Evolutionary Genomics at the Human–Environment Interface in Africa. (3rd June 2020) - Svardal, Hannes; Rusuwa, Bosco; Linderoth, Tyler; Kiran, Anmol; Charmantier, Anne; Lattorff, H Michael G; Cagan, Alex; Ommeh, Sheila C; Kamng'ona, Arox; Katongo, Cyprian; Santos, M Emília; Durbin, Richard; et al.
Abstract: We report on the first meeting of SMBE in Africa. SMBE Malawi was initiated to bring together African and international researchers who use genetics or genomics to study natural systems impacted by human activities. The goals of this conference were 1) to reach a world-class standard of science with a large number of contributions from Africa, 2) to initiate exchange between African and international researchers, and 3) to identify challenges and opportunities for evolutionary genomics research in Africa. As repored, we think that we have achieved these goals and make suggestions on the way forward for African evolutionary genomics research.